X3 Futurenet Cafe / Al-Haziq Faizal Othman … [et al.] - Othman, Al-Haziq Faizal; Ahmad Rafa’ee, Ashraf; Hamazimin, Aryna Athirah; Mohamad Abu Bakar, Hanie Amirah; Lamat, Abdul Khalid; Mohamad Saifullah, Taufiq (2014)
X3 Futurenetcafe is a start-up cyber cafe located in Kuching, Sarawak. X3 Futurenetcafe expects to catch the interest of a regular loyal customer base with its broad variety of games and printing services. The company plans to build a strong market position in the town, due to the partners industry experience and mild competitive climate in the area. X3 Futurenetcafe aims to offer its products at a competitive price to meet the demand ofthe middle-to higher-income local market area residents and students.